Surgical Management of Cardiac Masses in Right Atrium Among Bone Sarcoma Pediatric Patients With Totally Implanted Ports - Zhou, Chenliang; Wang, Yiyun; Chen, Zonghui; Qian, Guowei; Yu, Wenxi; Wang, Yong; Zheng, Shuier; Shen, Zan; Li, Hongtao; Wang, Yonggang (Frontiers in Oncology, 2022)
Introduction: Totally implanted ports (PORTs) have been widely used among patients with malignancy. Cardiac metastasis secondary to bone sarcoma and catheter-related right atrial thrombosis (CRAT) can be both present as cardiac masses. However, these two cardiac masses share very similar imaging characteristics. Methods: The features, treatments, and outcomes of 5 bone sarcoma pediatric patients with PORTs who suffered from cardiac masses in the right atrium were analyzed. Clinical data and histological characteristics of cardiac masses were also recorded. Results: Among 928 patients with malignancy and PORTs, 5 bone sarcoma pediatric patients were found to have cardiac masses in the right atrium. The catheter tips were located in the right atrium of 4 patients and the superior vena cava-right atrium junction (CAJ) of 1 patient. Four patients with good responses to anti-tumor treatment had received surgical lumpectomies for pathologic identification and mass excision, with cardiac metastases among 1 patient and thromboses among 3 patients. The median time from venous access port implantation to cardiac mass detection for CRAT was 6.3 months (range: 4.7–6.8 months) and to diagnosis of or possible cardiac metastasis was 13.3 months (range: 11.2–15.4 months). Conclusion: The placement of a catheter tip into the right atrium should be avoided. The time from PORTs implantation to cardiac mass detection might serve as a potential tool to differentiate cardiac metastasis from CRAT. Surgical management may be an effective treatment for bone sarcoma pediatric patients who had good responses to anti-tumor treatment and suffered from cardiac masses in the right atrium.